Corrigendum to “Synthesis and biological evaluation of Halogen-Substituted novel α-Ketoamides as potential protein aggregation modulators in Alzheimer's disease” [Bioorg. Chem. 147 (2024) 107373](S0045206824002785)(10.1016/j.bioorg.2024.107373) - Das B.; Baidya A.T.K.; Chakrabarti S.; Chouhan D.; Thakur B.; Darreh-Shori T.; Chen G.; Tiwari V.; Kumar R. (My University, 2025)
The authors regret that in Fig. S2 (Appendix A. Supplementary data, page no. 3) one of the micrographs labelled BD27 was incorrect. It was inadvertently duplicated and placed in both the BD24 and BD27. The corrected Fig. S2 is provided below.[Figure presented] Fig. S2. Morphological changes in SHSY-5Y cells observed under an inverted light microscope (10× magnification). The scale bar is of 50 µM. The authors also regret that in Appendix A. Supplementary data (page no. 33) the 13C NMR spectrum was repeated both for 1H NMR and 13C NMR for compound BD17. The 1H NMR spectrum for the compound BD17 is given below. 1H NMR of BD17[Figure presented] The authors would like to apologise for any inconvenience caused. © 2025 Elsevier Inc.